Returns on German Stocks 1954 to 2013 - Richard Stehle; Martin H. Schmidt (Credit and Capital Markets – Kredit und Kapital, 2015)
Existing time series of the returns on German stocks are either short or have weaknesses. We discuss the problems of creating such a time series and then report our monthly series based on all stocks in the top segment of the Frankfurt Stock Exchange. We compare our return series with the returns implied by major German stock market indices. In each of the four sub-periods we look at, which together cover the full 60 years, our time series is fully in line with at least one of the indices. In addition to looking at nominal rates of return we look at real returns and at excess returns with respect to the one-month money market interest rate. We show that the riskiness of a 20-year investment in German stocks, measured by the frequency of negative excess returns, has not increased but rather decreased since the middle of the 1960s. – – Renditen deutscher Aktien 1954 bis 2013 Existierende Zeitreihen der Renditen deutscher Aktien sind entweder kurz oder haben Schwächen. Wir erörtern zuerst die Probleme der Erstellung solcher Reihen, dann präsentieren wir unsere eigene monatliche Zeitreihe, die auf allen Aktien des obersten Segments der Frankfurter Börse basiert. Wir vergleichen unsere Zeitreihe mit den Renditen, welche die wichtigsten deutschen Aktienindizes implizieren. In jeder der vier untersuchten Unterperioden, die zusammen die gesamten 60 Jahre umfassen, steht unsere Reihe voll im Einklang mit zumindest einem in der Unterperiode existierenden Vergleichsindex. Wir betrachten zusätzlich zu den nominalen Renditen auch die realen Renditen und die Überrenditen im Vergleich zum Geldmarktzins für einmonatige Anlagen. Wir zeigen, dass das Risiko von 20-jährigen Anlagen in deutsche Aktien, gemessen mit der Häufigkeit von negativen Überrenditen, sich seit Mitte der sechziger Jahre nicht erhöhte, sondern eher verringerte.
Keywords: G10; 330; Germany; market portfolio; market index; long-term return; data quality; stock market peculiarities; CDAX